Eskimo Boyhood : An Autobiography in Psychosocial Perspective - Kakianak, Nathan (Book collections on Project MUSE., 1974)
Story of an Eskimo growing up on St. Lawrence Island during 1930's and 1940's and an analysis of the major trends in socio-cultural change in a small and isolated corner of the world.